Thermal and pCO2 Stress Elicit Divergent Transcriptomic Responses in a Resilient Coral - Davies, Sarah W.; Marchetti, Adrian; Ries, Justin B.; Castillo, Karl D. (Frontiers in Marine Science, 2016)
The oceans are becoming warmer and more acidic as a result of rising atmospheric pCO2. Transcriptome plasticity may facilitate marine organisms’ acclimation to thermal and acidification stress by tailoring gene expression to mitigate the impacts of these stressors. Here, we produce the first transcriptome of the abundant, ubiquitous, and resilient Caribbean reef-building coral Siderastrea siderea, and investigate this corals’ transcriptomic response to 95 days of thermal (T = 25, 28, 32°C) and CO2-induced acidification (324, 477, 604, 2553 µatm) stress. The S. siderea transcriptome was assembled using RNAseq and then Weighted Gene Correlation Network Analysis was employed to obtain systems-level insights into the coral’s stress response. Exposure of the coral to both elevated temperature and acidification elicited strong but divergent transcriptomic responses. Gene Ontology analysis suggests that long-term thermal stress disrupts homeostasis by increasing transcription of protein-coding genes associated with protein catabolism and suppressing transcription of genes involved in responding to environmental stimuli. Both next century (604 µatm) and extreme-high (2553 µatm) pCO2 stress increased transcription of genes associated with respiration, highlighting the potentially greater energetic requirements of maintaining calcification under high-pCO2 conditions. Under extreme-high-pCO2, increased transcription of H+-transporter genes was observed, consistent with the proposed role of proton transport in facilitating coral calcification under elevated pCO2. These results suggest that 95 days of exposure to 32°C seawater elicits a more adverse transcriptomic response (i.e., broad scale reductions in gene expression) than exposure to extreme-high acidification (2553 µatm; i.e., increased expression of genes associated with ion transport) within S. siderea—with the response to extreme warming suggesting cellular shutdown and the response to extreme acidification indicating capacity for acclimation. These results are consistent with the observation that rates of net calcification for the investigated corals were more negatively affected by the prescribed thermal stress than by the prescribed acidification stress. This study demonstrates how transcriptome plasticity may promote coral acclimation to these global change stressors, but that there are limits to the efficacy of this plasticity.